Organised Crime Groups involved in Fraud - May, Tiggey (Crime Prevention and Security Management, 2018)
Through analysis of data held by the National Crime Agency on organised crime groups, and in-depth analysis of qualitative interviews with convicted fraudsters and enforcement professionals, this detailed study fills a significant gap in the contemporary literature on organised crime groups involved in fraud. Throughout the chapters, the perspective of convicted offenders and those involved in its policing are juxtaposed to show the ease of committing fraud from the perspective of offenders on the one hand, and the investigative challenges experienced by law enforcement officers on the other. May and Bhardwa's insights shed light on offender motivations, routes into fraud and organised crime, and the nature and shape of organised crime groups and their operations. Alongside the offender perspective the law enforcement interviews provide a unique interpretation of the procedural and legislative weaknesses that appear to allow this type of offender to make considerable financial gain. The key recommendations based on empirical findings will greatly benefit those interested in understanding the links between fraud and organised crime in the UK and those seeking to improve enforcement efforts. .